Gambaran Strategi Mengajar Instruktur pada Mata Pelajaran Matematika Tingkat SMP di Lembaga Bimbingan Belajar Jhon's Febby Kota Padang - Yollanda Yollanda; Irmawita Irmawita (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2018)
Background of this research is nilai of matematic is good. This research is a descriptive study, with a population of student in Jhon’s Febby population totaling IS 80 people, the sample was taken 60% of the population, namely 48 people with a sampling technique that is stratified random sampling. Techniques using questionnaires, and data collection tools using questionnaires. Data analysis techniques use a percentage formula. The results showed that the description of the earning stratigic l in learning methodwas very good category, the aproved of thelearning strategic its was very good category, and thelearning teknique its was very good. It is suggested to Instructors to improve the application of practice methods on initial activities, core activities and evaluation activities, and for other researchers to be able to examine other factors that have not been examined in this study relating to the application of practice methods.Keywords: Learning, Strategic